The Ethics of Responsibility as aChallenge to Philosophy in the Modem World - Ströker, Elizabeth (1999)
The ethics of responsibility presents itself today as a"new" ethics in the age of science and technology, against traditional ethics of duties. lts advantage is that, in the notion of responsibility, several related members may be distinguished: a subject of responsibility (individual or collective), a state-of-affairs and its consequences to respond to, and an instance of responsibility regarding which the subject is accountable. Yet the ethics of responsibility can only be effective if it reassumes determinations of the traditional ethics of duties, quite severed from it.